Establishment of the European forage collection ”To age with AEGIS”: A report from the ECPGR/AEGIS workshop, 30 January - 3 February 2012, Research Centre for Agrobiodiversity, Hungary - Veteläinen, M. (2012)
A report from the ECPGR/AEGIS workshop - Establishment of the European Forage Collection, 30th January- 3rd February 2012, Research Centre for Agrobiodiversity, Hungary